(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The article does not present the results of research on the influence of 25–100% whey on the properties of gelatin, the time of gel formation at different temperatures, and the quality of the fruit and vegetable jelly enriched with whey. The effect of whey on the moisture-retaining capacity of gelatin was studied on model systems. It has been shown that replacing a percentage of water with whey results in a 15.5-50.0% reduction in gelatin’s ability to retain absorbed moisture compared to a sample soaked in 100% water. It should be noted that the increase in serum in the system caused a decrease in the ability of gelatin to retain absorbed moisture. In addition, it was found that with an increase in the amount of milk serum, already in the real system, the time of gel formation at 18 ℃ is lengthened by 11.1–50.0%, and at a temperature of 5 ℃ – by 25.0–66.0% compared to the control. This is most likely due to a change in the concentration of the solution used for soaking gelatin, because it is known that gelatin dissolves well in water, absorbing 10 times more moisture than its own weight. It is possible that the chemical composition of the serum, rich in fats, proteins and minerals, affects the rearrangement of molecular chains and the formation of a weaker spiral network. Experimental studies proved that the strength of the gel in the obtained fruit and vegetable jelly is 5.3–42.8% lower compared to the control sample. Jelly moisture increased by 5.3–16.7% with increasing serum in the system, while acidity, on the contrary, decreased by 7.1–25.0% compared to the control sample. According to organoleptic indicators, the consistency of jelly with milk whey was evaluated with the lowest points, but the indicators of taste and aftertaste in such products improved with an increase in the amount of whey. Therefore, in order to avoid the negative impact of whey on the jelly structure, it is suggested to consider the possibility of increasing the amount of gelatin in the recipe or selling such a product packaged in a rigid consumer container.